Tyrosine-phosphorylated Vav1 as a Point of Integration for T-cell Receptor- and CD28-mediated Activation of JNK, p38, and Interleukin-2 Transcription - Hehner, Steffen Peter; Hofmann, Thomas G.; Dröge, Wulf (The journal of biological chemistry, 2000)
In this study we identified tyrosine-phosphorylated Vav1 as an early point of integration between the signaling routes triggered by the T-cell receptor and CD28 in human T-cell leukemia cells. Costimulation resulted in a prolonged and sustained phosphorylation and membrane localization of Vav1 in comparison to T-cell receptor activation alone. T-cell stimulation induced the recruitment of Vav1 to an inducible multiprotein T-cell activation signaling complex at the plasma membrane. Vav1 activated the mitogen-activated protein kinases JNK and p38. The Vav1-mediated activation of JNK employed a pathway involving Rac, HPK1, MLK3, and MKK7. The costimulation-induced activation of p38 was inhibited by dominant negative forms of Vav1, Rac, and MKK6. Here we show that Vav1 also induces transcription factors that bind to the CD28RE/AP element contained in the interleukin-2 promoter. A detailed mutational analysis of Vav1 revealed a series of constitutively active and nonfunctional forms of Vav1. Almost all inactive versions were mutated in their Dbl homology domain and behaved as dominant negative mutants that impaired costimulation-induced activation of JNK, p38, and CD28RE/AP-dependent transcription. In contrast to NF-AT-dependent transcription, Vav1-mediated transcriptional induction of the CD28RE/AP element in the interleukin-2 promoter could only partially be inhibited by cyclosporin A, suggesting a dual role of Vav1 for controlling Ca2+-dependent and -independent events.
Gesehen am 03.02.2021